A geo-political analysis of the Corona pandemic and its relationship to the economies of countries, the Kingdom of Saudi Arabia and Qatar as a model (Journal of Misan Researches, 2021)
At the beginning of 2020, the world experienced a new crisis in light of the spread of the Corona pandemic COVID-19, as the first spark of the pandemic was launched from the second largest global economy and the engine of global economic growth, which is the Chinese economy, and the wide-ranging economic impacts we have on the global economy in all its aspects, such as the collapse of global stock exchanges and the decline in oil prices in global markets in an unprecedented manner despite the historical stations that have passed through the fluctuation of global oil prices, and the complete closure of the majority of companies and global markets. This study was launched with a number of hypotheses, the most important of which is the occurrence of some economic repercussions on the Kingdom of Saudi Arabia and the State of Qatar as a result of the drop in oil prices as It represents the main resource for these countries, and the study reached a number of results, the most important of which is that the Saudi and Qatari economies face two fundamental challenges at the same time, as is the case in renter economies, which is the spread of the Corona pandemic COVID 19 and the sharp decline in global oil prices, producing countries, including Saudi Arabia and the State of Qatar, as Total actual revenues amounted to about (728) billion riyals, down from the previous budget approved, amounting to (833) billion riyals in 2020 in the Kingdom of Saudi Arabia, while the State of Qatar, in 2019, the total actual revenues in its budget amounted to about (217) billion riyals, which decreased in 2020 to about (171.2) billion riyals due to the Corona pandemic and the drop in oil prices. The price of a barrel of oil globally amounted to about (55) dollars in the month of February (the second) in 2020, it descended to its lowest level in the month (the fourth), as it reached (about 17.7) dollars per barrel of the same year. The researcher used the analytical method that analyzes the strength of The country in terms of geographical and economic terms and the impact of the COVID-19 pandemic and its economic repercussions on the Kingdom of Saudi Arabia and the State of Qatar.